Diversification Benefits of Commodity Investments – Evidence from Finnish Stock Market - Kähkölä, Anniina (My University, 2012)
The purpose of this study is to investigate the potential diversification benefits of commodity investments for stock investors in the Finnish stock market. According to portfolio theory, investors are able to lower the overall risk of their portfolio by combining securities that don't have perfectly positively correlated returns. A central factor in stock pricing theory is earnings that affect companies' dividends, free cash flow and added value, all of which are numerators in stock pricing models. Commodity prices, on the other hand, are determined by demand and supply. Increasing commodity prices increase companies' production costs, but it is not always possible for companies to adjust their selling prices on a short notice. This results in lower earnings, which in turn lead to decreasing stock prices. Similarly, decreasing commodity prices lower companies' production costs, which lead to higher earnings and stock prices. This indicates that commodity returns might have low or even negative correlation with stock prices, which creates diversification benefits. OMX Helsinki 25 index represents the Finnish stock market as well as a portfolio that is maintainable for a private investor. Two of the most widely known commodity indexes, Dow Jones-UBS Commodity Index and Standard & Poor's Goldman Sachs Commodity Index represent the commodity markets. The sample period covers years from 1991 to 2011. Diversification benefits are investigated through Pearson's product moment correlation coefficient, which measures the linear dependency between variables. Sharpe ratio is used in measuring the risk-adjusted performance of portfolios. The results show that the correlation between stock- and commodity returns is very low on monthly and yearly horizons, which indicates that diversification benefits exist between these asset classes. Any combination of stocks and commodities would outperform an all-stock portfolio over the sample period. During the weakest months on stock markets, commodities don't offer positive returns, but they do outperform stocks. Different commodity groups are found to offer different levels of diversification benefits; precious metals and agricultural commodities have the lowest return correlations with stocks.
Keywords: Commodity; commodity index; portfolio theory; diversification; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|